Characterization and prognostic implication of delayed complete response in AL amyloidosis. (4th December 2020) - Muchtar, Eli; Gertz, Morie A.; Kumar, Shaji K.; Lacy, Martha Q.; Leung, Nelson; Buadi, Francis K.; Dingli, David; Hayman, Suzanne R.; Go, Ronald S.; Kapoor, Prashant; Gonsalves, Wilson; Kourelis, Taxiarchis V.; et al.
Abstract: Introduction: Little is known on continued response following completion of therapy in light chain (AL) amyloidosis. Methods: We studied 373 AL amyloidosis patients who achieved complete response (CR) or very good partial response (VGPR) to first‐line therapy. Results: By end of therapy (EOT), 46% of patients achieved a CR and 54% a VGPR. With no further therapy, 17.5% of patients were upstaged from VGPR to CR (delayed CR), with a median of 9 months. Compared with CR and VGPR at EOT, patients with a delayed CR were characterized by higher proportion of t (11;14) and lower rate of trisomies. Autologous stem cell transplant was more frequent in the delayed CR group. Patients with a delayed CR were characterized by minimal residual disease negativity and organ response rates similar to patients with CR at EOT and higher than patients achieving VGPR at EOT. Patients with a delayed CR had a longer PFS/OS compared to patients with CR or VGPR by EOT (median PFS 149 vs 92 vs 52 months, P  < .001; 10‐year OS 87% vs 71% vs 56%, P  < .001). Conclusions: This study characterizes delayed CR in AL amyloidosis, highlights its prognostic impact which is at least similar to those who achieved CR at EOT, and underlines another aspect of response monitoring.